Biotechnological Avenues in Mineral Processing: Fundamentals, Applications and Advances in Bioleaching and Bio-beneficiation. (2nd January 2023) - Mishra, Srabani; Panda, Sandeep; Akcil, Ata; Dembele, Seydou
ABSTRACT: Mineral biotechnological applications, e.g., bioleaching and bio-beneficiation, for waste treatment and resource recovery have invited due attention owing to their economic and eco-friendly benefits in comparison to the conventional methods. Although research has progressed well, there are several aspects that are still not well understood and require more attention in view of full-scale industrial application of these processes. For example, microbe-mineral/galvanic interactions, passivation phenomenon, synergistic effects among the microbes, identification of novel and robust microbial strains, etc., require more studies to explore the fundamental aspects. In addition, mode of treatment for a wide variety of ores and/or concentrates, advances in engineering applications and scaling-up of bio-processes to industrial level along with the assessment of techno-economic feasibility, life-cycle, and environmental impact can provide numerous opportunities for the researchers to further explore the applied aspects. This paper presents comprehensive details, including the latest research, on the fundamentals and applications of bioleaching, bioflotation and bioflocculation for the readers. The key microorganisms and their mode of action, factors affecting each bio-processes and aspects related to their scale-up and industrial applications are reviewed, analyzed and compared. It is believed that the recent advances, emerging dimensions and future directions of research presented in this paper will serve as a guide for the researchers to further explore this exciting field of research.